Il “grande ritorno” dell’educazione civica a scuola: struttura, funzioni, limiti e potenzialità (durante la pandemia) - Ferro Allodola, Valerio (Studi sulla Formazione/Open Journal of Education, 2021)
The article intends to highlight the structure, functions, limits and potential of Civic Education in the Primary school curriculum. Introduced with Law 92 of 08/20/2019, the discipline entered the classrooms starting from the school year following the date of entry into force of the Law, i.e. from September 2020, in the pandemic period. In this article, the historical excursus of Civic Education in Italy is reconstructed, starting from the work of the Constituent Assembly up to the present day. The structure given by the D.M. 35 of 22 June 2020, with the three annexes contained, highlighting the potential and problematic issues that must be quickly solved for its application from kindergarten to Secondary school.